The Effect of the Task-based Learning Strategy on Developing the Values of Patience among Second-grade Intermediate School Students - Ismail, Alia Safaa (Journal of Tikrit University for Humanities, 2023)
The aim of the research is to know the effect of the task-based learning strategy in developing the values ​​of patience among second-grade intermediate students. The research sample consisted of (120) second-grade intermediate students. The researcher used the experimental approach and divided the sample into two groups, the experimental group and the control group, and before the initiation of teaching rewarded the researcher with a number of variables, and prepared the research tool represented by the patience values ​​scale, which consisted of (20) items. The equation of Alpha Cronbach and the results showed the superiority of the experimental group students in the post-patience values ​​scale test, as well as the presence of differences between the pre and post application of the patience values ​​scale among the experimental group students and in favor of the post test, and the researcher came up with a number of recommendations and suggested a number of proposals.